Clinical Spectrum of Herpes Simplex Keratitis in a Tertiary Eye Hospital, Nepal - Shrestha, Poonam; Paudel, Santosh (Journal of Karnali Academy of Health Sciences, 2023)
Background: Ocular manifestations of herpes simplex virus infection range from benign blepharitis, conjunctivitis, and epithelial keratitis to vision-threatening stromal keratitis and uveitis. This study aims to find out the demographic profile, clinical manifestations of herpes simplex virus keratitis and to assess associated visual impairment in Nepalese population. Methods: The retrospective study was conducted from January 2020 – February 2022. The medical records were reviewed where visual acuity at presentation and at one month follow-up, clinical details on examination and, diagnosis of the stage of disease were noted. Results: Of 112 herpes simplex keratitis patients, mean age was 47.19±19.14 years. Patients of herpes simplex keratiris presented with different types of clinical manifestations namely 25 (22.31%) cases were dendritic and 13 (11.6%) geographic ulcers, 38 (33.9%) cases presented with purely stromal lesions, 19 (16.9%) cases with epithelial plus stromal lesions, 11 (9.8%) cases with stromal plus endothelial lesions and six (5.3%) cases with endothelitis. At presentation, 33 (29.4) had visual acuity of 6/6–6/18, 50 (44.6%) had 6/18–6/60, 6 (5.3%) had 6/60–3/60 and 23 (20.5%) had <3/60. At one month follow up 71 (63.3%) had visual acuity of 6/6–6/18, 30 (26.7%) had 6/18–6/60, 5 (4.4%) had <6/60–3/60 and 6 (5.35%) had <3/60. Conclusion: Herpes simplex keratitis has diverse presentation and can cause significant vision impairment. Early clinical diagnosis and management may prevent disease progression and visual impairment.